A critical analysis of the prognostic performance of the 8th edition American Joint Committee on Cancer staging for metastatic cutaneous squamous cell carcinoma of the head and neck. Issue 6 (19th January 2019) - Sood, Ashish; Wykes, James; Roshan, David; Wang, Laura Y.; McGuinness, John; Fowler, Allan; Ebrahimi, Ardalan
Abstract: Background: The 8th edition AJCC staging of cutaneous squamous cell carcinoma of the head and neck (cSCCHN) incorporated extranodal extension (ENE) for the first time. This study compared the prognostic performance of the 7th and 8th edition staging for cSCCHN with nodal metastases. Methods: Retrospective analysis of 96 patients with metastatic cSCCHN, comparing the ability of staging systems to predict disease‐specific and overall survival (OS) using the proportion of variation explained and Harrell's C‐index. Results: In AJCC8, the N classification was upstaged in 77% of patients due to the presence of ENE and 88% of patients were classified as TNM stage IV. AJCC8 was inferior to AJCC7 in predicting disease‐specific survival for both N and TNM stages, and OS by TNM stage. Conclusions: The majority of patients with metastatic cSCCHN have ENE and are classified as TNM stage IV based on the 8th edition staging, resulting in poor prognostic performance.